Extraction, purification, structural characterization, and antioxidant activity of a novel polysaccharide from Lonicera japonica Thunb. - An, Feiyu; Ren, Guangyu; Wu, Junrui; Cao, Kaixin; Li, Mo; Liu, Yumeng; Liu, Yanfeng; Hu, Xinyu; Song, Meijun; Wu, Rina (Frontiers in Nutrition, 2022)
A novel water-soluble polysaccharide (HEP-4) with a molecular weight of 1.98×105 Da was extracted from honeysuckle. Structural characterization wasperformed using high-performance liquid chromatography (HPLC), gas chromatography, Fourier transform-infrared (FT-IR) spectrum, nucleus magnetic resonance (NMR) spectra, and scanning electron microscopy. The results showed that HEP-4 is primarily composed of mannose, rhamnose, galacturonic acid, glucose, galactose, and arabinose with a mole ratio of 6.74:1.56:1.04:14.21:4.31:5.4, and the major types of the glycosidic bond types of HEP-4 were 1-α-D-Glcp, 1,4-β-D-Glcp, 1-β-D-Arap, 1,3,4-β-D-Arap, and 1,3,6-β-D-Man. The results of bioactivity experiments revealed that HEP-4 had antioxidant in vitro. In addition, HEP-4 inhibited H2O2-induced oxidative damage and increased the activity of HepG2 cells by reducing MDA levels and inhibiting ROS production. Meanwhile, HEP-4 significantly enhanced the activities of GSH-Px and CAT, indicating that HEP-4 exerts a protective effect on H2O2-induced oxidative stress. These results indicate that HEP-4 could be a potential natural antioxidant.